Could anyone point me in the right direction with these two questions, I am lost on where to start.
An=-An-1, a0 = 5 (Note: n-1 is a subscript)
An=An-1 + 3, a0 = 1
Hello, vexiked1
You haven't told us what we're supposed to do.
But I'll assume we want the formula for the term.
It says: each term is the negative of the preceding term.
So the sequence is: .
The general term is: .
It says: Each term is three more than the preceding term.
So the sequence is: .
The general term is: .
My apologies.... I am to find the solution to the recurrence relations with the given initial conditions. So does this still apply? So the basic approach is to find the sequence first then?
I am also having trouble with:
An=2An-1 -3, a0 = -1
An=(n+1)An-1, a0=2
An=2nAn-1, a0=3
An=-An-1 + n - 1, a0 = 7